2012
DOI: 10.1007/s00396-012-2864-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol effects on the gelation behavior of α-tocopherol acetate-encapsulated ethosomes with water-soluble polymers

Abstract: This work aims at understanding the ethanol effects on the gelation behavior of ethosomes with the consideration of encapsulating a hydrophobic material. Gelation of the empty ethosomes by positively charged watersoluble polymers with and without hydrophobic modification, respectively, was systematically studied first for the effects of solution dielectric constant and gelator concentration on the phase map and rheological property of the mixtures. A comparison of the gelation behavior of empty and α-tocophero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
(71 reference statements)
0
4
0
1
Order By: Relevance
“…Hal ini sejalan dengan hasil yang diperoleh yaitu %EE maksimum terdapat pada formula C (etanol 40%) dan %EE minimum terdapat pada formula D (etanol 20%). Beberapa studi melaporkan bahwa konsentrasi optimal etanol dalam pengembangan sistem etosom yang stabil adalah sekitar 30-40% [28][29][30] . Perlu dicatat bahwa penggunaan etanol di atas 40% menyebabkan vesikel menjadi sangat permeabel sehingga dapat terjadi 'kebocoran' yang kemudian menurunkan nilai %EE 27 .…”
Section: Pembahasanunclassified
“…Hal ini sejalan dengan hasil yang diperoleh yaitu %EE maksimum terdapat pada formula C (etanol 40%) dan %EE minimum terdapat pada formula D (etanol 20%). Beberapa studi melaporkan bahwa konsentrasi optimal etanol dalam pengembangan sistem etosom yang stabil adalah sekitar 30-40% [28][29][30] . Perlu dicatat bahwa penggunaan etanol di atas 40% menyebabkan vesikel menjadi sangat permeabel sehingga dapat terjadi 'kebocoran' yang kemudian menurunkan nilai %EE 27 .…”
Section: Pembahasanunclassified
“…A two-fold increase in ethanol concentration resulted in a yield decrease to 16 +/− 5.6%. It has been shown that increasing the alcohol concentration reduces the stiffness of the lipid particles [43]. Many other medicinal substances are enclosed in the ethosome including quercetin [44] and rutin [45].…”
Section: Antioxidants and Flavonoidsmentioning
confidence: 99%
“…However, optimization of concentration of ethanol in ethosomal systems is somewhat obligatory in terms of vesicle size, entrapment efficiency, stability, safety, etc. A wide range of investigational studies have reported 30-40% as an optimal range of ethanol in the development of stable and successful ethosomes (Limsuwan & Amnuaikit, 2012;Chiu et al, 2013;Zhao et al, 2013). Studies have reported the increment in the size of vesicle by ethanol concentration range of 20-45% Elsayed et al, 2007) etc.…”
Section: Alcohol and Effects Of Its Elevated Concentrationsmentioning
confidence: 99%